The Well-Being Situation in Latin America - Rojas, Mariano (Springer Link, 2024)
Latin Americans report high life satisfaction levels; as a region Latin America has the highest mean life satisfaction in the world. The affective situation of Latin Americans is also outstandingly high. The many political and socio-economic problems reflect on average life evaluation levels. Cultural factors associated to family satisfaction and satisfaction in relational domains play an important role in explaining high life satisfaction in Latin America. Some intra-region differences exist and the average figures cannot be extended to the whole population or to all the countries in the region.
Keywords: well-being; situation; Latin America; WOS(2)